Jaccoud's arthropathy--diagnostic and therapeutic implications. Issue 756 (October 1988) - Thakur, R.; Gupta, L. C.; Misra, M.; Saran, R. K.; Hasan, M.
Abstract : A case of isolated chronic severe aortic regurgitation with Jaccoud's arthropathy involving the foot is presented. The interesting feature of the case is the absence of history of acute rheumatic arthritis at any stage of the illness. The diagnostic and possible therapeutic significance of this otherwise uncommon and benign condition are discussed.